P06-08 Socio-demographic profile of physically inactive adults living in Italy according to the PASSI data. (29th August 2022) - Minardi, Valentina; Possenti, Valentina; Gallo, Rosaria; Contoli, Benedetta; Lana, Susanna; Masocco, Maria
Abstract: Background: Insufficient physical activity (PA) or physical inactivity (PI) is one of the ten leading risk factors for global mortality. PI leads to 20-30% increased risk of all-cause mortality and monitoring its current levels and trends in general population is essential to track progress towards health targets, identify at-risk groups, assess policies' effectiveness, guide future planning. Methods: PASSI (Progressi delle Aziende Sanitarie per la Salute in Italia - Progresses in ASSessing adult population health in Italy) is an ongoing cross-sectional Behavioral Risk Factor Surveillance System (BRFSS) that monitors prevalence and temporal trends for the major modifiable health-related risk factors in the adults (18-69 years) residing in Italy. Data are collected in the Local Health Units (LHU) by trained personnel who administer a standardized questionnaire telephonically to sampled people. In the period 2015-2018, 132, 717 people were interviewed in more of 90% LHUs (89 out of 101 in 2018), achieving a response rate above 80%. Concerning PA/PI, respondents are classified as per the WHO indicators in: (i) Active - basing on levels achieved in leisure time and/or heavy work; (ii) Partially active - in leisure time and/or moderate work or in spare time and without regular work; (iii) Inactive - in leisure time with sedentary work or in spare time and without regular work. PASSI calculates prevalence of PA/PI overall and by socio-demographic characteristics, including 95% confidence intervals (CI), and a logistic regression model estimates adjusted prevalence ratios (APR). Results: In Italy, 28.8% (CI95%:28.5-29.1%) of adult population is featured by a sedentary lifestyle: PI is greater among women (32.4% vs. 25.1%; APR: 1.26), grows with age (34% in over50 vs. 24.7% among 18-34 year-old; APR: 1.34), is higher among deprived people both per economic difficulties (41.7% if many vs. 22.4% if none; APR: 1.39) and for education level (23.7% university vs. 47.2% primary/any; APR: 1.33). We observed a highly evident geographic gradient: PI amounts to 18.3% in the North, 25.2% in the Centre and 40.6% in the South. A multivariate analysis confirms these values are statistically significant. Conclusions: PASSI data provide strong evidence to support community prevention interventions on territorial planning or advice by health professionals.